ANTIBACTERIAL ACTIVITY EXTRACT SEA GRAPE (Caulerpa racemosa) AGAINTS Micrococcus luteus AND Klebsiella pneumoniae - Hainil, Sri; Mawardi Badar; Marliza, Hesti; Rastria Meilanda; Apriyani Efendi (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Research on the antibacterial activity of Sea Grapes (Caulerpa racemosa) against Klebsiella pneumoniae and Micrococcus luteus is crucial due to the significant potential hazards posed by these bacteria. Klebsiella pneumoniae, a Gram-negative bacterium, can cause serious infections in the urinary and respiratory tracts, while Micrococcus luteus, a Gram-positive bacterium, often infects the skin of fish and humans. Sea Grapes, found in various Indonesian waters, contain secondary metabolites with potential as bioactive compounds in pharmaceuticals, including antibacterial, antiviral, and antifungal agents. The high alkaloid content, especially Caulerpin, in C. racemosa demonstrates substantial potential for developing new antibacterial agents. Although previous research has shown moderate antibacterial activity against Staphylococcus aureus and ineffectiveness against Escherichia coli, further exploration of other bacteria such as Klebsiella pneumoniae and Micrococcus luteus could open new opportunities for discovering effective antibacterial compounds. The purpose of this research to know antibacterial activity fractions of sea grapes. The bacteria used were Micrococcus luteus and Klebsiella pneumoniae. The method used is paper disc diffusion method. The antibacterial activity was tested using extract with concentration 25%, 75%, 100% and used a positive control Tetracycline 30 g/paper disk and a negative control using DMSO 10%. The results of the extract tested were the most active as an antibacterial extract with a concentration of 100% on Micrococcus luteus bacteria with an inhibitory power of 16.7 mm and on Klebsiella pneumoniae bacteria which had an inhibitory power of 12.1% mm. The conclusion of this reseach the extract had antibacterial activity